A putative spermidine synthase interacts with flagellar switch protein FliM and regulates motility in Helicobacter pylori. Issue 5 (21st September 2017) - Zhang, Huawei; Lam, Kwok Ho; Lam, Wendy Wai Ling; Wong, Sandra Yuen Yuen; Chan, Vera Sau Fong; Au, Shannon Wing Ngor
Summary: The flagellar motor is an important virulence factor in infection by many bacterial pathogens. Motor function can be modulated by chemotactic proteins and recently appreciated proteins that are not part of the flagellar or chemotaxis systems. How these latter proteins affect flagellar activity is not fully understood. Here, we identified spermidine synthase SpeE as an interacting partner of switch protein FliM in Helicobacter pylori using pull‐down assay and mass spectrometry. To understand how SpeE contributes to flagellar motility, a speE ‐null mutant was generated and its motility behavior was evaluated. We found that deletion of SpeE did not affect flagellar formation, but induced clockwise rotation bias. We further determined the crystal structure of the FliM‐SpeE complex at 2.7 Å resolution. SpeE dimer binds to FliM with micromolar binding affinity, and their interaction is mediated through the β1' and β2' region of FliM middle domain. The FliM‐SpeE binding interface partially overlaps with the FliM surface that interacts with FliG and is essential for proper flagellar rotational switching. By a combination of protein sequence conservation analysis and pull‐down assays using FliM and SpeE orthologues in E . coli, our data suggest that FliM‐SpeE association is unique to Helicobacter species. Abstract : Putative spermidine synthase SpeE was identified as an interacting partner of motor switch protein FliM in H . pylori . The key residues were identified based on the 2.7 Å crystal structure of SpeE‐FliMM complex. SpeE is found necessary for normal motility and proper flagellar rotational switching in H . pylori . This work provides a novel regulation mechanism of bacterial motility.